Peran Saintek Terhadap Pembelajaran Fisika - Perdana, Dimas Halim; Septi, Lidya; Rahmadani, Okta Dewi Tryshita; Mahardika, I Ketut; Ernasari, Ernasari; Handono, Sri (Jurnal Ilmiah Wahana Pendidikan, 2024)
In the digital age, the application of technology in physics learning plays an important role. Technology helps students understand physical concepts interactively and visually, enhances learning motivation, and enriches experiences with multimedia content. However, there are also negative impacts such as the lack of social interaction and the risk of dependence on technology. The use of technology in physics learning opens up opportunities for collaboration, develops digital skills, and expands access to physical learning. It’s important to apply technology wisely and accurately. Keywords: Science, Collaboration, Development